Role of University Strategic Initiatives in Service and Infrastructure Model to Develop the City of State Corporation "Rosatom" Presence Using VЕTI NRNU MEPhI as an Example - V. A. Rudenko; N. F. Privalova; S. A. Tomilin; T. S. Popova (Глобальная ядерная безопасность)
The paper considers the model of service and infrastructure development of the city of Volgodonsk which is based on the approach that takes into account the existing potential in the territory of the urban agglomeration and is aimed at a more intensive use of available opportunities. As a result of the implementation of the Strategy of its socio-economic development until 2030, the city of Volgodonsk should become a city of scientific and technical intellectuals. And an important role in achieving this mission is assigned to the Volgodonsk Engineering and Technical Institute (branch of MEPhI). This university is considered as a driver of "intellectual prosperity" of the Rostov NPP location. VITI MEPhI translates in the region the interests of MEPhI as a strategic partner of SC "Rosatom" in the field of personnel training. The development strategy of VITI MEPhI is aimed at preservation and multiplication of the achieved results taking into account modern trends of education development and establishes key objectives, tasks, specific directions, mechanisms ensuring further development of the Institute at the present stage of functioning of the system of higher professional education.